Mental health illness in chronic respiratory disease is associated with worse respiratory health and low engagement with non‐pharmacological psychological interventions. Issue 3 (18th March 2021) - Hunter, Roseanna; Barson, Elizabeth; Willis, Karen; Smallwood, Natasha
Abstract: Patients with chronic respiratory disease commonly experience comorbid mental illness. This study aimed to explore associations between mental illness and respiratory health, as well as determine access to and uptake of mental health treatment. Mental health conditions were highly prevalent, long‐standing and associated with worse respiratory outcomes. Active treatment with psychotropic drugs was common; however, acceptance of non‐pharmacological interventions was poor. Further research is required to understand co‐existing mental illness management in chronic respiratory disease.